Corrosion-induced cracking time in recycled aggregate concrete (RAC) - Paewchompoo, Nattapong; Yodsudjai, Wanchai; Suwanvitaya, Prasert; Iwanami, Mitsuyasu; Boonyingsathit, Nutpakan; Thaue, Wiracha; Kiattanabumrung, Supisara (Engineering and Applied Science Research, 2020)
The objective of this research was to determine the influence of using recycled concrete aggregates (RCA) on the time for corrosion-induced cracking. Three levels of replacement by recycled aggregates were adopted, i.e., 0%, 50% and 100% by volume. Corrosion of reinforcement was accelerated using DC current. The compressive and tensile strengths were also investigated. The results showed that the reinforcement mass losses of the RCA were 2.5% and 2.4% higher than those of the NAC for 50% and 100% replacement, respectively. The corrosion-induced cracking times of the RAC were 5.6% and 8.6% longer than those of the NAC for 50% and 100% replacement, respectively. Additionally, the Maaddawy’s and Modified Maaddawy’s models were found to be acceptable for predicting concrete cover cracking time.